2021
DOI: 10.1111/xen.12706
|View full text |Cite
|
Sign up to set email alerts
|

Xenotransplantation of tannic acid‐encapsulated neonatal porcine islets decreases proinflammatory innate immune responses

Abstract: Background: Islet transplantation with neonatal porcine islets (NPIs) is a promising treatment for type 1 diabetes (T1D), but immune rejection poses a major hurdle for clinical use. Innate immune-derived reactive oxygen species (ROS) synthesis can facilitate islet xenograft destruction and enhance adaptive immune responses. Methods: To suppress ROS-mediated xenograft destruction, we utilized nanothin encapsulation materials composed of multilayers of tannic acid (TA), an antioxidant, and a neutral polymer, pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…These approaches include induction of localized immunosuppression by encapsulating islets with antioxidant-containing nanothin coatings to decrease oxidative stress ( 46 ), incorporating dexamethasone-eluting micelles to suppress inflammatory responses ( 47 ) or by cotransplanting BAT-derived MSCs to further induce Treg differentiation ( 42 ). Additionally, BAT is a promising extrahepatic transplant site for other sources of insulin-producing β cells such as stem cell-derived β cells ( 48 51 ) or genetically modified xenogeneic porcine islets ( 52 57 ), both of which have demonstrated promise. However, the maximum possible islet number for a single BAT depot would have to be defined in both these preclinical models and also in human BAT to determine if the higher number of islet equivalents needed in these alternative approaches would be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches include induction of localized immunosuppression by encapsulating islets with antioxidant-containing nanothin coatings to decrease oxidative stress ( 46 ), incorporating dexamethasone-eluting micelles to suppress inflammatory responses ( 47 ) or by cotransplanting BAT-derived MSCs to further induce Treg differentiation ( 42 ). Additionally, BAT is a promising extrahepatic transplant site for other sources of insulin-producing β cells such as stem cell-derived β cells ( 48 51 ) or genetically modified xenogeneic porcine islets ( 52 57 ), both of which have demonstrated promise. However, the maximum possible islet number for a single BAT depot would have to be defined in both these preclinical models and also in human BAT to determine if the higher number of islet equivalents needed in these alternative approaches would be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…By using TA, antioxidants and neutral polymer poly(n-vinylpyrrolidone) (PVPON) multilayers to form a nano-thin encapsulation material PVPON/TA. After xenografting, PVPON/TA-encapsulated neonatal porcine islets were not defective in glucose responsiveness and had reduced expression of MHC-II and co-stimulatory molecules CD40, CD80 and CD86 in antigen-presenting cells ( 129 ).…”
Section: Anti-inflammatory Hydrogelsmentioning
confidence: 99%
“…1,2,7,16,17,22,24,25 Several studies have shown that subcutaneous transplantation sites can be modified to promote neovascularization posttransplantation. These methods involve the use of biologics such as growth factors (beta-fibroblast growth factor [FGF], vascular endothelial growth factor), [26][27][28] chemical modifications of the encapsulation material, 29 anti-inflammatory drugs, 14,30,31 co-delivery of mesenchymal stem cells, [32][33][34] and the use of oxygen generators, 10,[35][36][37] among others.…”
Section: Introductionmentioning
confidence: 99%